Protection from the pink mealybug - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Pink Mealybug. Protocols for the Protection of Agricultural Production and Trade By R D Gautam, R N Pilgrim & V E Stewart, CARDI & CTA, 2000. 60 pp. ISBN 976 617 007 x CTA number 1018 . 5 credit points